Shunting operation in the complex treatment of children with cerebellum medulloblastoma - Orlov, Y. A.; Shaverskiy, A. V.; Plavskiy, N. V. (Ukrainian Neurosurgical Journal, 2005)
The results of 60 patients with medulloblastoma treatment are presented. The shunting operations were used before the tumor removal, during the removal and after, with the main goal — to correct intracranial hypertension. The shunting operations are the part of the complex treatment, applied at patients with cerebellum medulloblastoma.